Pengaruh Kemudahan Penggunaan, Keamanan, Kepercayaan Terhadap Keputusan Pembelian Secara Online pada Aplikasi Shopeedi Kota Pekanbaru - Pebrianti; Ulfiah Novita (Al-Manar Journal of Accountancy and Business Studies, 2024)
Shopee is a leading marketplace platform and e-commerce site in Indonesia and Southeast Asia. SEA Group (formerly known as Garena) was founded by Forrest Li in 2009 and currently manages Shopee. Purchasing decisions are crucial for Shopee as they measure the extent of purchases on the platform. The objective of this research is to determine the influence of Ease of Use, Security, and Trust on Online Purchasing Decisions on the Shopee Application in the city of Pekanbaru. The population in this study includes all residents of Pekanbaru who have the Shopee application. The sampling method used in this research is the Lameshow technique, which selects samples based on specific considerations. The data used are primary and secondary data. The data analysis method employed is multiple linear regression. The results indicate that Ease of Use, Security, and Trust influence Online Purchasing Decisions on the Shopee Application in the city. The coefficient of determination shows that the variables Ease of Use (XI), Security (X2), and Trust (X3) have a positive but not significant effect on the purchase decision variable (Y).